Surplus to Requirements: Work, Non-Linearity, and Abduction in Creative Research - Madero, María Angélica; Carney, James (Imaginations)

(untitled) (York University, 2024)
We argue that the institutional administration of academic and creative research as labor does violence to the true character of this research as work. Where work is a pluralist concept that admits multiple forms of transformation, labor is based on a linear proportionality of inputs to outputs. We explore various forms of non-linearity in creative work and pedagogical work, ranging across disproportion, the associative, the counterfactual, and the interdisciplinary. We arrive at C.S. Peirce’s notion of semiotic abduction as a useful cognitive model for research practice and creation. Here, the linear mapping of inputs to outputs is complemented by a recognition of the role played by the speculative or interpretive leap in arriving at novel concepts and practices.